Destination Development for Rural Tourism Area in Wanayasa, Puwakarta, West Java, Indonesia - Gunawijaya, Jajang; Pratiwi, Annisa (E-Journal of Tourism; Volume 3 Number 2 (September 2016), 2016)
This purpose of this paper is to elaborate the understanding of destination development of rural tourism in Wanayasa, Purwakarta, Jawa Barat. It has a rich potential for the rural tourism prosperity. Then author incorporates destination development through Butler‘s Area Life Cycle. Research was conducted in August 2015 with qualitative approaches i.e. interview and focus group discussion to 120 respondents which comprises representation from several different group. In addition, some of data also produced from secondary sources such as government regulation and official website. Findings show that Wanayasa possessed their ability in developing aspect of internal factors, attractions and accommodation facilities. Apart from that quality, it is obvious that their rural tourism development is lack of destination management and chaotic strategy marketing formulation as a result of disorganized planning processes. With those conditions, it will be tough for them to formulate the true competitive advantage as a basic foundation of their tourism development. This paper illustrates a detailed analysis of the destination‘s strengths and weaknesses, and a more distinctive understanding of what facilitates a destination‘s competitive position.
Keywords: destination development; life cycle tourism; rural tourism development; Wanayasa